Pengembangan Teknologi Pengemasan Untuk Meningkatkan Daya Saing Produk Olahan Berbasis Bahan Baku Daging Dan Jamur Tiram Di Desa Watu Kec. Marioriwawo, Kab. Soppeng, Sulawesi Selatan - Muhammad Irfan Said; Renny Fatmyah Utamy; Sutomo Syawal; Miah Said (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
One of the main challenges faced by partners is their limited knowledge regarding product packaging, particularly for processed meat and oyster mushroom-based chips. The objective of this activity was to improve partners' capacity and skills in selecting packaging types and carrying out product packaging processes, both for processed meat and chips. The activity was conducted in Watu Village, Marioriwawo District, Soppeng Regency, South Sulawesi. The partners involved were the "Kampung Baru" Women's Farmers/Livestock Group. The activity consisted of outreach, training, practice, and evaluation. The results of this activity indicate that the training and practice activities carried out by partners have proven effective in increasing capacity, knowledge, and skills in selecting packaging types and carrying out the packaging process. Packaging has been proven to increase product value, provide consumer appeal, and provide external protection, thus enhancing product competitiveness in the market.